Comprehensive Sexuality Education for Adolescents in Zambia via the Mobile-Optimized Website TuneMe: A Content Analysis. Issue 1 (2nd January 2020) - Rogers, Erin; Hemal, Kshipra; Tembo, Zangose; Mukanu, Mulenga; Mbizvo, Michael; Bellows, Benjamin
Abstract: Adolescents in sub-Saharan Africa encounter high risks associated with sexuality and reproduction, yet face numerous barriers in obtaining appropriate health services and information. Mobile phones provide a unique opportunity to provide youth with this critical sexual and reproductive health information need. Designed from the United Nations Comprehensive Sexuality Education framework, the mobile-optimized app TuneMe aims to provide adolescents living in eight sub-Saharan African countries—Zambia, Malawi, Zimbabwe, Swaziland, Lesotho, South Africa, Botswana, and Namibia—with sexual and reproductive health information, and to promote uptake and use of sexual and reproductive health services. To assess the scope and appropriateness of TuneMe's sexuality education content, we conducted a directed content analysis of the 299 articles published on the Zambia-specific TuneMe site between October 2015 and June 2017. Results from this analysis indicate that the greatest information provided by TuneMe was on sexual and reproductive health and HIV, followed by relationships, sexual rights, and citizenship. There was substantially less information that focused specifically on matters of pleasure, violence, diversity, and gender. Content was situated within relatable and culturally-relevant contexts, but gave mixed, and often problematic, depictions of gender norms. This assessment is central to understanding current and future mobile-based sexuality education programming.